Carbohydrate recognition using metal-ligand assemblies - Ahamed, Rafiq; Venkatesh, Jayashree; Srithar, Rakshantha; Gaikwad, Sudhakar; Pramanik, Susnata (Organic & Biomolecular Chemistry, 2023)
Carbohydrate-binding proteins, known as lectins, play a wide range of vital roles in cellular and pathological processes. Mimicking lectins to achieve specific molecular recognition of carbohydrates in organic and aqueous media using artificial receptors is challenging due to the synthetic hurdles of receptors and structural similarities between sugars. Carbohydrate recognition using non-covalent interactions remains a vast topic. This review summarises the recognition of carbohydrates using metal-ligand assemblies, including metallosupramolecules, macrocycles, and cages. It also highlights the challenges and future directions in the field.